Spoken words as biomarkers: using machine learning to gain insight into communication as a predictor of anxiety. (6th May 2020) - Demiris, George; Corey Magan, Kristin L; Parker Oliver, Debra; Washington, Karla T; Chadwick, Chad; Voigt, Jeffrey D; Brotherton, Sam; Naylor, Mary D
Abstract: Objective: The goal of this study was to explore whether features of recorded and transcribed audio communication data extracted by machine learning algorithms can be used to train a classifier for anxiety. Materials and Methods: We used a secondary data set generated by a clinical trial examining problem-solving therapy for hospice caregivers consisting of 140 transcripts of multiple, sequential conversations between an interviewer and a family caregiver along with standardized assessments of anxiety prior to each session; 98 of these transcripts (70%) served as the training set, holding the remaining 30% of the data for evaluation. Results: A classifier for anxiety was developed relying on language-based features. An 86% precision, 78% recall, 81% accuracy, and 84% specificity were achieved with the use of the trained classifiers. High anxiety inflections were found among recently bereaved caregivers and were usually connected to issues related to transitioning out of the caregiving role. This analysis highlighted the impact of lowering anxiety by increasing reciprocity between interviewers and caregivers. Conclusion: Verbal communication can provide a platform for machine learning tools to highlight and predict behavioral health indicators and trends.